PENGARUH KUALITAS LAYANAN, LOKASI DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN (Studi pada Pelanggan Hotel Horison Semarang) - Dini Oktaviani, 15.05.51.0304; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the influence of service quality, location and company image on customer satisfaction. The population in this study were customers of the Horison Hotel Semarang. The sampling method used in this study was purposive sampling. The sample in this research is 100 customers of Semarang Horison Hotel who have made lodging more than 2 times. Data collection through questionnaires using a Likert scale 5 (five) alternative answers. Testing instruments using validity which shows the results of the value of KMO >0.5 and the value of loading factor >0.4 and reliability which shows the Cronbach alpha value> 0.70. Based on the results of the study, the regression equation was found as follows: Y = 0.147X1 + 0.321X2 + 0.476X3 + ℯ. The most powerful variable is company image (0.476) and followed by location (0.321) and the last is service quality (0.147). Model testing using the coefficient of determination and F (goodness of fit) test. At the value of of 0.711 which shows that 71.1 percent of customer satisfaction can be explained by variables of service quality, location and company image. Testing the hypothesis in this study using the t test. The variables used in this study are service quality, location, company image and customer satisfaction. The results showed that service quality has a positive and significant effect on customer satisfaction, location has a positive and significant effect on customer satisfaction and the company's image has a positive and significant effect on customer satisfaction.